O débito de gratidão do rei como fundamento político jurídico das doações de sesmaria: o caso da capitania do Ceará (1679-1682) - Mateus, Rafael Cronje (2023)
One finds, in the Portuguese America’s sources related with land donations, through the application of the legal institute of sesmarias, the claim that donations were owed to the supplicants due to the services they had provided to the Crown and the king. What, at first glance, may be seen as unreasonable allegations, given their recurrence, requires investigation in order to be understood. This dissertation, starting from the case of sesmaria donations that took place in the Captaincy of Siará, from 1679 to 1682, sought in the political and legal literature of the medieval and Old Regime the reasons that supported these allegations. After a brief study of the institute of sesmarias and its translation to the American space of the Portuguese Empire, the place of the debt of gratitude in Portuguese political thought, in the political reality of the government, and in the legal institutes of the Order of Grace are investigated. We then turn to sesmaria donations, which are now seen as having a political and legal basis in what the king owed to his subjects who graciously provided him with services. The king's debt of gratitude needed to be paid, and donations of land, through sesmaria, were one of the types of payment.